Cyber Risk Mitigation Strategy and Data Privacy in Sharia Mobile Banking Applications for Generation Z Customer Retention - maulanazakariaahmad; Ahmad Roziq (ISTIFADA : Jurnal Ekonomi dan Lembaga Keuangan Syariah, 2026)
Rapidly development sharia mobile banking services have increase convenience access transaction finance for society , especially Generation Z who have digital native characteristics and levels dependence tall to technology . However , the increase use digital services are also followed by increasing threat risk cyber risk, such as phishing, malware, theft identity , personal data leaks , and various form attack cyber others that have potential lower trust customers . Research This aim For analyze the influence of mitigation strategies risk cyber and protection The impact of data privacy on Generation Z customer retention on Islamic mobile banking applications . Research use approach quantitative with method survey against 250 respondents Generation Z which is users active Islamic mobile banking in Indonesia. The technique of taking sample using purposive sampling, whereas data analysis was carried out with Structural Equation Modeling - Partial Least Squares (SEM-PLS). Variable independent includes mitigation strategies risk cyber and data privacy, while customer retention as variables dependent . Research results show that mitigation strategy risk cyber influential positive and significant towards customer retention with coefficient track of 0.412 (p < 0.001). Protection data privacy also has an impact positive and significant towards customer retention with coefficient of 0.376 (p < 0.001). In general simultaneous second variables capable explains 61.8% of the variation in customer retention (R² = 0.618). Findings This show that improvement system digital security , implementation authentication layered , data encryption , fraud detection based on intelligence artificial , transparency personal data management , as well as compliance to regulations data protection becomes factor important in maintain loyalty customers Generation Z. Implications study confirm that Islamic banks need integrate aspect security cyber , data protection , and sharia values such as trustworthiness , transparency , and protection right customers For create ecosystem safe , reliable , and sustainable digital services